Advanced Care Planning and End-of-life Outcomes in Hematopoietic Stem Cell Transplant Patients. (August 2021) - Cooper, Alexandra; Dains, Joyce E.
Aim/Purpose: This integrative review addresses whether the presence and timing of advanced care planning (ACP) with or without a palliative care (PC) consultation affect place of death and use of high-intensity medical care at end-of-life (EOL) in adolescent and young adult and adult cancer patients receiving hematopoietic stem cell transplant (HSCT) therapy. Methods and Results: A literature search was completed in the Scopus and PubMed databases. The search was not restricted by date but was restricted to English language. A total of 1, 616 articles were found, and after exclusion of duplicates and irrelevance, 79 articles were available to review. After reviewing inclusion and exclusion criteria, 9 articles related to ACP with HSCT were found, and 4 were eliminated after further review, resulting in 5 viable articles for review related to EOL outcomes. EOL outcomes reviewed were place of death and high-intensity medical care. Factors noted to influence these measures included the presence or absence of ACP, the timing of ACP, and PC consultation. Overall survival also emerged as an EOL outcome affected by ACP. Conclusion: Although there have been many barriers identified to ACP discussions in the HSCT population, the findings from the integrative literature review support the use of early ACP with patients who have hematologic malignancies undergoing HSCT to address patient EOL goals and reduce healthcare utilization at the EOL. The data also suggest that identification of patients who would most benefit from early engagement in ACP may positively impact outcomes.